The correlation between mangrove density and suspended sediment transport in Lamreh Estuary, Mesjid Raya Subdistrict, Aceh Besar, Indonesia. (December 2018) - Permatasari, I; Dewiyanti, I; Purnawan, S; Yuni, S M; Irham, M; Setiawan, I
Abstract: Abrasion and sedimentation of mangrove land transfer in Lamreh estuary is believed to reduce the marine productivity. The objectives of the study were to determine the relationship between mangrove density and suspended sediment transport occurred in the coastal area of Lamreh Estuary. Sampling was conducted on March until May 2014, three substations were established in this site. The 1 st Substation was toward the sea, the 2 nd substation was in the middle land and the 3 rd substation was toward the land. Square transects method used for mangrove sampling and sediment trap used to ensnare sediment. Three species found in this area were Rhizophora apiculata, Bruguiera gymnorhiza, and Avicennia marina . Furthermore, Rhizophora apiculata dominated in this area. The highest density was Bruguiera gymnorhiza with average 11 ind/100m 2 and the lowest density was Heritiera littoralis with average 1 ind/100m 2 in the 2 nd substation. The highest sediment transport was in 1 st substation and the lowest was in the 3 rd substation. Sediment transport in the 1 st substation for one month was 5.54 to 6.63 g/cm 2 /day with mangrove density was 12 ind/100m 2 and sediment transport in the 3 rd substation was 4.87 to 5.52g/cm 2 /day with mangrove density was 32 ind/100m 2 . The correlation between mangrove density and suspended sediment transport in this area was a negative correlation with the correlation between the two coefficients was ranged from -0.999-0.863 till. The Negative correlation was indicated resources would the high density decrease mangrove sediment transport and the opposite.